Comparison of short- and long-term effectiveness of ixekizumab and secukinumab in real-world practice. (1st February 2021) - Caldarola, Giacomo; Mariani, Marco; Pirro, Federico; Nicolotti, Nicola; Burlando, Martina; Calabrese, Laura; Parodi, Aurora; Peris, Ketty; De Simone, Clara
ABSTRACT: Background : Although secukinumab and ixekizumab both act by inhibiting IL-17A, some scientific evidence suggests that there are differences in efficacy between the two agents. Objective : The aim of this study was to compare the short- and long-term effectiveness of ixekizumab and secukinumab in clinical practice. Methods : A retrospective study was conducted on a cohort of 245 psoriatic patients receiving secukinumab or ixekizumab during the period from September 2016 to December 2019. The proportion of patients achieving PASI75, PASI90, and PASI100 at weeks 12 and 24 was calculated. We recorded the 12- and 24-month drug survival as a measure to assess long-term effectiveness. Results : A higher proportion of patients in the secukinumab group achieved PASI75, 90, and 100 at 12 weeks. The Kaplan-Meier survival curve for any reason of discontinuation showed no differences between the two groups. Instead, the multivariate analysis for ineffectiveness, adjusted for potential confounders, showed a lower drug survival rate in the secukinumab group, with an adjusted HR of 2.57 (95% CI 1.05–6.28, p 0.038). Conclusion : This real-life study demonstrated that ixekizumab and secukinumab are both highly effective in short- and long-term treatment of psoriasis, even though few differences exist concerning speed of action and long-term effectiveness.